Detection of ESBL and MBL in non fermenting gram negative bacilli isolated from a tertiary care hospital - Tariq Ahmad Shah; P. Preethishree; Shima Simon (Al Ameen Journal of Medical Sciences)
Background: NFGNB either do not use carbohydrates as a source of energy or degrade them through metabolic pathways other than fermentation. They are innately resistant to many antibiotics and are known to produce ESBL and MBL that limits therapeutic options. Our objectives were to identify the NFGNB and to determine their Antibiogram, including ESBL and MBL detection. Methods: The study included 91 NFGNBs isolated from clinical samples, identified by conventional method. AST was done by Kirby Bauer disk diffusion method. ESBL detection was performed by DDST method and MBL detection by Imipenem-EDTA combined disc test, as per CLSI Guidelines. Results: NFGNB were predominantly isolated from swabs (41%), pus (20.87%) and sputum (20.87%). P.aeruginosa (69.23%) was the predominant isolate followed by A.baumanii (27.49%), S.maltophilia (2.19%), and B.cepacia (1.09%). 46% of the isolates were ESBL producers (60 % P.aeruginosa, 28% A.baumannii, all isolates of B.cepacia and S.maltophilia). Approximately 20% NFGNB were MBL producers (17.46% P.aeruginosa and 16% A.baumanii, 4.34% S.maltophilia and all isolates of B.cepacia). Conclusion: Early detection of ESBL and MBL, evaluation of effective antibiotic option, prudent use of antibiotics by formulating antibiotic policy and infection control measures would assist in the effective management of patients.